The role of programming code sharing in improving the transparency of medical research - Schultze, Anna; Tazare, John (BMJ (Online), 2023)
[...]considering the retraction of several Surgisphere articles,7 a code sharing mandate might have flagged concerns with these papers earlier, given how difficult it would be to generate code for data management and analysis that never took place. 10.1093/aje/kwad007 36627249 3 Morton C Devito N Morley J. Software development skills for health data researchers. Prevalence and predictors of data and code sharing in the medical and health sciences: systematic review with meta-analysis of individual participant data.